Coherence Trade-off relations in Multipartite systems. (September 2016) - Radhakrishnan, Chandrashekar; Parthasarathy, Manikandan; Jambulingam, Segar; Byrnes, Tim
Abstract: Quantum coherence is investigated using a new measure with metric properties and entropic nature and decomposed into local and intrinsic contributions. The trade-off relation between these contributions as well as their distribution properties are studied for simple tripartite systems and the more complex spin chain model. We find that the coherence changes its nature with respect to the parameters of the quantum state under investigation.